Rational Design of Fluorescent Phthalazinone Derivatives for One‐ and Two‐Photon Imaging. Issue 35 (21st July 2016) - Yang, Lingfei; Zhu, Yuanjun; Shui, Mengyang; Zhou, Tongliang; Cai, Yuanbo; Wang, Wei; Xu, Fengrong; Niu, Yan; Wang, Chao; Zhang, Jun‐Long; Xu, Ping; Yuan, Lan; et al.
Abstract: Phthalazinone derivatives were designed as optical probes for one‐ and two‐photon fluorescence microscopy imaging. The design strategy involves stepwise extension and modification of pyridazinone by 1) expansion of pyridazinone to phthalazinone, a larger conjugated system, as the electron acceptor, 2) coupling of electron‐donating aromatic groups such as N, N ‐diethylaminophenyl, thienyl, naphthyl, and quinolyl to the phthalazinone, and 3) anchoring of an alkyl chain to the phthalazinone with various terminal substituents such as triphenylphosphonio, morpholino, triethylammonio, N ‐methylimidazolio, pyrrolidino, and piperidino. Theoretical calculations were utilized to verify the initial design. The desired fluorescent probes were synthesized by two different routes in considerable yields. Twenty‐two phthalazinone derivatives were synthesized and their photophysical properties were measured. Selected compounds were applied in cell imaging, and valuable information was obtained. Furthermore, the designed compounds showed excellent performance in two‐photon microscopic imaging of mouse brain slices. Abstract : Better probes by design : A pyridazinone/phthalazinone library of one‐ and two‐photon emissive probes for use in live‐cell and brain‐tissue imaging (see figure) was constructed. The electronic states of the N ‐substituents of the pyridazinone/phthalazinone moieties effectively modulate the photophysical properties of the fluorescent probes, and the terminal groups on the alkyl chain determine the lipophilicity and subcellular organelle selectivity.